2018
DOI: 10.1080/15548627.2018.1427396
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol and multilamellar bodies: Lysosomal dysfunction in GBA-Parkinson disease

Abstract: Lipid and cholesterol metabolism might play a role in the pathogenesis of Parkinson disease (PD). However, the association between cholesterol and PD is not clearly established. Cholesterol accumulation is closely related to the expression of multilamellar bodies (MLBs). Also, cholesterol controls autophagosome transport. Thus, impaired cholesterol and autophagosome trafficking might lead to robust autophagic vacuole accumulation. Our recent work provides the first evidence that the presence of the N370S GBA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 0 publications
3
57
0
1
Order By: Relevance
“…Likewise, a-Syn aggregates might impair the autophagic-lysosomal pathway function (Xilouri et al, 2013a), establishing a reciprocal relationship. The accumulation of a-Syn reduces lysosomal degradation capacity b y d i s r u p t i n g h y d r o l a s e s t r a ffi c k i n g , s u c h a s o f glucocerebrosidase 1 (GCase1), from the endoplasmic reticulum to the lysosome (Mazzulli et al, 2011;García-Sanz et al, 2017;García-Sanz et al, 2018). Currently, mutations in the GBA1 gene are the main genetic risk factor for PD.…”
Section: Propagation Of Alpha-synuclein: Evidence and Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a-Syn aggregates might impair the autophagic-lysosomal pathway function (Xilouri et al, 2013a), establishing a reciprocal relationship. The accumulation of a-Syn reduces lysosomal degradation capacity b y d i s r u p t i n g h y d r o l a s e s t r a ffi c k i n g , s u c h a s o f glucocerebrosidase 1 (GCase1), from the endoplasmic reticulum to the lysosome (Mazzulli et al, 2011;García-Sanz et al, 2017;García-Sanz et al, 2018). Currently, mutations in the GBA1 gene are the main genetic risk factor for PD.…”
Section: Propagation Of Alpha-synuclein: Evidence and Considerationsmentioning
confidence: 99%
“…GBA1 mutations result in reduced enzymatic activity that leads to the accumulation of glucosylceramide and of cholesterol and its esters in lysosomes, which can compromise lysosomal function and promote a-Syn aggregation, creating a bidirectional loop (Schapira, 2015). Previous studies from our laboratory have shown that fibroblasts derived from PD patients with the GBA1 mutation accumulate cholesterol in lysosomes and present multilamellar bodies (García-Sanz et al, 2017;García-Sanz et al, 2018). Also, membrane structures resembling lysosomes and autophagosomes have been found in the inner architecture of Lewy bodies (Shahmoradian et al, 2019), suggesting that the alteration of these organelles might contribute to the formation of Lewy bodies.…”
Section: Propagation Of Alpha-synuclein: Evidence and Considerationsmentioning
confidence: 99%
“…The accumulated MLBs have been proposed to be related to deficiency of fusion of autophagosomes with lysosomes or/and lysosomal disorders, 57,58 which eventually disturbs autophagy flux. 58,[85][86][87] It appears that there are potentially more than one mechanisms through which, high Pi reduces autophagy flux. High Pi decreases autophagosome formation through promoting beclin 1/BCL2 complex, and impairs autophagosome-lysosome function consequently blocking autophagosome and autolysosome recycling.…”
Section: High Phosphate Suppresses Autophagy Fluxmentioning
confidence: 99%
“…We show in the present study that these glucosylceramides are increased in the DRGs of Pink1SNCA mice strengthening the idea that they contribute to the pathology of sensory neurons. Mutations of GBA1, the key lysosomal enzyme catalyzing GlcCer degradation, have been associated with autophagolysosmal dysfunctions [66,67], increased alpha-synuclein toxicity [27,68] and disruptions of mitochondrial energy production [49]. GBA1 expression was unaltered in the DRGs of Pink1SNCA mice, and the ultrastructural morphology of lysosomes and lipid droplets in DRG neurons appeared to be normal for the age.…”
Section: Discussionmentioning
confidence: 99%